Windjammers and Sea Tramps - Runciman, Walter Runciman, Baron, 1847-1937 (Salt Lake City, UT : Project Gutenberg, 2005)
"Windjammers and Sea Tramps" by Walter Runciman is a historical account written in the early 20th century. The book provides insights into the lives of sailors and the evolution of seamanship, reflecting on the experiences of those who worked in England's mercantile marine over several centuries. It examines the shifts in culture, superstitions, and the changing conditions faced by seamen, addressing both the romanticism and harsh realities of life at sea. At the start of the narrative, the author introduces his background and experiences in the maritime world, asserting that his insights are drawn from personal encounters and historical context. He presents the character of sailors, emphasizing their bravery but also their brutal treatment and the superstitions that pervaded their lives. Through anecdotes and commentary, Runciman sets the stage to explore the complexities of seamanship and the evolution of attitudes towards sailors from the time of legendary figures like Drake and Hawkins to the early 20th century, as he critiques contemporary sailors and their conditions. (This is an automatically generated summary.)
Introductory -- Peculiar and uneducated -- A cabin-boy's start at sea -- The seaman's superstitions -- The seaman's religion -- Safety and comfort at sea -- Wages and wives -- Life among the packet rats -- Brutality at sea -- Bravery -- Chanties -- Jack in ratcliffe highway -- The matter-of-fact sailor -- Resourcefulness and shipwreck -- Manning the service.
Release date is 2005-02-23
Produced by Steven Gibbs and the Online Distributed Proofreading Team.
Keywords: Seafaring life